2000
DOI: 10.1016/s0925-4773(99)00307-x
|View full text |Cite
|
Sign up to set email alerts
|

SRY, SOX9, and DAX1 expression patterns during human sex determination and gonadal development

Abstract: SRY, SOX9, and DAX1 are key genes in human sex determination, by virtue of their associated male-to-female sex reversal phenotypes when mutated (SRY, SOX9) or over-expressed (DAX1). During human sex determination, SRY is expressed in 46,XY gonads coincident with sex cord formation, but also persists as nuclear protein within Sertoli cells at 18 weeks gestation. High-level SOX9 expression in the sex cords of the testis parallels that seen during mouse development, however in humans, SOX9 transcripts also are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
187
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(215 citation statements)
references
References 14 publications
16
187
0
6
Order By: Relevance
“…Although this study reports our findings using PCR subtractive hybridization, we have since confirmed our findings on SOX9 using DNA microarray analysis. We show here that SOX9, which is essential for chondrogenesis (Bell et al, 1997;Bi et al, 1999;Healy et al, 1999;Olney et al, 1999) and male sexual differentiation (Graves, 1998;Hanley et al, 2000;Hawkins, 1995;Koopman, 1999Koopman, , 2001, is induced by RAR pan-agonists and an RARa selective agonist in retinoid-inhibited breast cancer cell lines. RAR-agonists have been reported to have divergent effects on the regulation of SOX9 in other cells.…”
Section: Discussionmentioning
confidence: 79%
“…Although this study reports our findings using PCR subtractive hybridization, we have since confirmed our findings on SOX9 using DNA microarray analysis. We show here that SOX9, which is essential for chondrogenesis (Bell et al, 1997;Bi et al, 1999;Healy et al, 1999;Olney et al, 1999) and male sexual differentiation (Graves, 1998;Hanley et al, 2000;Hawkins, 1995;Koopman, 1999Koopman, , 2001, is induced by RAR pan-agonists and an RARa selective agonist in retinoid-inhibited breast cancer cell lines. RAR-agonists have been reported to have divergent effects on the regulation of SOX9 in other cells.…”
Section: Discussionmentioning
confidence: 79%
“…In humans, WT1 expression first appears at 32 days postovulation (d.p.o. ) in the gonadal ridges of both male and female embryos and then increases at 41 d.p.o., whereas SRY is most strongly expressed at 44 d.p.o., and both genes are expressed later in fetal development (Hanley et al, 1999(Hanley et al, , 2000. Furthermore, mutations in both genes are associated with gonadal dysgenesis in mice and humans as described above.…”
mentioning
confidence: 89%
“…Thus, Sf1 and WT1 are required for gonadal formation. In testicular differentiation they have a synergistic action on the transcription of Sox9 (an autosomal gene closely related to Sry) and Mis (or Amh, anti-Mülle-rian hormone) that are both expressed in Sertolli cells of seminiferous cords [26,27]. In ovarian differentiation, Dax 1, by interacting with SF1, prevents the synergistic action of SF1 and WT1 and thus acts as a repressor of Sox9 and Mis transcription [28,29].…”
Section: Genes Involved In Gonadal Sex Differentiationmentioning
confidence: 99%